A current perspective on leishmaniasis - Angela Clem (Journal of Global Infectious Diseases, 2010)
There are many challenges facing the successful control and eradication of cutaneous and visceral leishmaniasis. Leishmaniasis is still endemic in many poverty stricken and war torn areas. Through the use of an extensive literature review, this article examined the global disease burden of cutaneous and visceral leishmaniasis. Surveillance and control measures for leishmaniasis being used by the World Health Organization were also discussed in this article. Finally, potential new treatments and possible vaccines for leishmaniasis were reviewed in this article.